Penerapan Prinsip-Prinsip Ekonomi Islam dalam Promosi Produk Hijab untuk Meningkatkan Penjualan pada Toko Annisa Kerudung (Studi Kasus: Pasar Aur Bukittinggi) - Dzaky Alfajri; Santi Deswita (ARZUSIN, 2026)
Although the application of Islamic economic principles in the promotion strategy of hijab products has received attention in several studies, research that specifically discusses the implementation of sharia values such as shiddiq, amanah, justice, and openness in promotional practices in microenterprises remains limited. This study aims to analyze the application of Islamic economic principles in promotional strategies and their relationship with increased sales at Toko Annisa Kerudung in Pasar Aur Bukittinggi. This study employed a qualitative approach with a case study design, involving informants consisting of the store owner and employees selected through a purposive sampling technique. Data were collected through semi-structured interviews, observation, and documentation, and were then analyzed using thematic analysis techniques through the stages of data reduction, data display, and conclusion drawing. The findings showed that the promotional strategy implemented included the promotion mix in the form of advertising, sales promotion, personal selling, direct marketing, and public relations. The application of Islamic economic principles has been carried out in several aspects, particularly through the delivery of honest and transparent product information to consumers. However, the implementation of these values has not been fully optimal because promotional approaches oriented toward hard selling are still found and have not fully integrated educational values in Muslim women’s dress. In addition, sales data fluctuating from year to year indicate that promotional effectiveness is determined not only by the intensity of promotional activities, but also by the quality of the values conveyed in marketing communication. These findings contribute to the development of sharia marketing theory by strengthening the integration between the promotion mix concept and Islamic economic principles and broadening understanding of the importance of the ethical dimension in marketing activities. The conclusion of this study confirms that the consistent application of the values of honesty, amanah, and justice in promotional strategies is important for increasing consumer trust and loyalty in the context of Muslim fashion businesses. The implications of this study include theoretical contributions to the enrichment of the value-based sharia marketing literature and practical implications for microenterprise actors in designing promotional strategies that are more effective, ethical, and sustainable.